Perencanaan Pajak PPh Badan untuk Efisiensi Beban Pajak Perusahaan pada CV Sukses Mitra Sejahtera - Alvira Zahra Siregar; Syamsul Bahri Arifin (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2026)
This article aims to analyze the implementation of tax planning by CV. Sukses Mitra Sejahtera in reducing Corporate Income Tax liabilities. The research employs communication and observation methods, with data collected through interviews, company documentation, literature study, and online information searching. The collected data were then analyzed using a qualitative descriptive approach, focusing on the processing of commercial and fiscal financial reports. The findings indicate that the company has not fully implemented tax planning optimally. However, the existing tax planning strategy has shown positive results, with a tax burden saving of IDR 3,994,865 or approximately 5.05% of the total income tax payable. These results demonstrate that, although not fully effective, tax planning can significantly contribute to reducing the company's tax burden. Therefore, tax planning proves to be an essential tool in enhancing the efficiency of tax liabilities, which can help companies achieve better and more sustainable financial management. This study provides valuable insights for other companies in implementing tax planning to maximize their tax savings.